Successful Treatment of Fetal Intraperitoneal Administration of Immunoglobulin in a Case of Fetal Hemolytic Anemia with 131, 072-Fold Anti-E Alloimmunization. (17th November 2011) - Yoshida, Masashi; Matsuda, Hideo; Hayata, Eijiro; Watanabe, Akio; Oeda, Miho; Furuya, Kenichi
Abstract : Object . We present here the case of severe fetal anemia caused by anti-E antibody positive, which showed a favorable course only with fetal intraperitoneal administration of immunoglobulin. Case . The mother was 31 years old, blood type B Rh : CCDee, gravida 1, with no history of transfusion. Anti-E antibody was detected in the maternal cross-match test at the 18th gestational week. In percutaneous umbilical blood sampling, the umbilical blood hemoglobin level was 9.1 g/dL and the result of the direct Coombs' test was positive at the 26th gestational week. Immunoglobulin injection into fetal abdominal cavity (IFAC) was administered a total 7 times. During the pregnancy, the indirect Coombs' test showed a 131, 072-fold increase. Conclusion . In this case, IFAC to block the reticuloendothelial system Fc receptor was successful. This procedure is promising as one of the treatment options for blood group incompatible pregnancy.